The influence of human resource competence and work motivation on the performance of employees of Public Appraisal Services Office - Andre Setya Bangsawan; Gogi Kurniawan (Junal Ilmu Manajemen, 2023)
This research investigates the influence of human resource competency dimensions and work motivation on employee performance at the Surabaya Branch of the Public Appraisal Services Office (KJPP). It aims to determine the primary factor impacting performance within. The study utilizes a census sampling technique due to the limited population size, with all 28 employees. The resulting regression model is expressed as: Y = 0.963 + 0.798(X1) + 0.446(X2), where the validity and reliability of indicators are assured. The model aligns with classical assumptions, emphasizing the predominant role of human resource competency (X1) with a coefficient of 0.798, followed by work motivation (X2) at 0.446. The findings indicate that the combined effect of human resource competency and work motivation significantly influences performance (69.907), thus confirming the research hypothesis. The partial correlation between human resource competency (X1), work motivation (X2), and employee performance (Y) is 0.921 (92.1%). R Square underscores a robust impact of human resource competency (X1) and work motivation (X2) on employee performance at (Y), registering at 0.848 (84.8%). In conclusion, this study underscores the vital roles of human resource competency and work motivation in shaping employee performance at.